ANALYSIS OF REMOTE SENSING DATA PERTAINING TO DEBRIS FLOWS: INSIGHTS FROM SELECTED DRAINAGE BASINS IN BULGARIA - Ilia Tamburadzhiev (Zbornik Radova: Geografski institut "Jovan Cvijić", 2024)
The present study is focused on remote sensing data analysis of the factors for the formation and development of debris flows in mountain drainage basins in Bulgaria. The rate of debris flow susceptibility in the range of the selected drainage basins was investigated. The relevance of the present study is related to the frequency of adverse hydro-climatic phenomena of natural and anthropogenic origin in the last decade in different parts of Bulgaria. Topographic conditions (slope angle), lithology, and land cover (vegetation) are considered as a complex area factor for the formation and development of debris flows. A morphometric analysis of the relief and the drainage network was carried out in order to analyze the debris flow susceptibility. Morphometric parameters and the Normalized Difference Vegetation Index (NDVI) were calculated in Geographic Information System (GIS) environment. The channel networks were classified by stream ordering. GIS analysis is done on the basis of Digital Elevation Model (DEM), Landsat multispectral satellite images, and geological maps. A complex debris flow susceptibility analysis was carried out. A classification system for debris flow susceptibility was generated. The complex analysis of the slope angle, lithology, and land cover within the studied basins show that drainage basins characterized predominantly by rocks of volcanic igneous complex and to a considerable extent by bare soils and arable lands are more susceptible to debris flows. The percentage of the highest rates of debris flow susceptibility is extremely low for the four studied drainage basins, which is largely due to the smaller slope gradients.